The brief COPE-A inventory in Russian for adolescents: Validation and evaluation of psychometric properties - Julia Marakshina; Georgy Vasin; Victoria Ismatullina; Artem Malykh; Timofey Adamovich; Marina Lobaskova; Sergey Malykh (Heliyon, 2023)
In this paper, the results of a psychometric analysis of a Brief Russian-language version of the COPE-A inventory for adolescents are presented. The inventory was designed for identifying coping strategies used in stressful situations and is comprised of 31 items. The study involved 3530 adolescents aged 13 to 17 years old. Using exploratory factor analysis and confirmatory factor analysis, it was shown that the data correspond to the expected six-factor configuration, but the distribution of items by factors differs from the theoretical structure. To improve the factor structure, two questions were excluded; the final version included 29 items. The resulting inventory’s scales turned out to be highly reliable (Cronbach's alpha values range from 0.72 to 0.89). Additionally, the construct validity of the method was assessed. In conclusion, the adapted version of the Brief COPE-A is suitable for use in the adolescent population.